Examining The Association Of Organophosphate Metabolites In Urine And Self-Reported Asthma And Asthma Attacks In Adults: A Re-Analysis Of Nhanes Results For 1999-2004 - Esdaille, Kyle Karlan Kern (My University, 2014)
Asthma is a major public health concern that has been increasing in prevalence over the last several decades. However, the cause of this chronic respiratory illness is still not clear to researchers. One suspected cause is exposure to organophosphate pesticides which were widely used to control pests in homes until 2004. The objective of this study is to determine the contribution of organophosphate pesticide exposure to asthma diagnosis and asthma attacks. Organophosphate exposure for the purposes of this study was based on measurements of urinary organophosphate metabolites of study participants. Specifically, the study examined whether higher levels of six urine metabolites increased the likelihood of asthma diagnosis and asthma attacks after adjusting for the effect modifiers of age, sex, race, income, education, BMI, smoking status and housing characteristics. The six organophosphate urine metabolites were grouped into three categories DMAPs, DEAPs, DAPs to account for potential interactions. Multiple logistic regressions were conducted to obtain odds ratios and 95% confidence intervals. The study results show those participants with the highest level of exposure to DMAPs, DEAPs and DAPs (DMAPs + DEAPs) are 2 times (OR= 2.11; 95% CI= 1.42, 3.15), 1.7 times (OR=1.67; 95% CI= 1.13, 2.47), and 1.8 times (OR=1.81; 95% CI= 1.16, 2.81) significantly (p<0.01) more likely to have an asthma diagnosis compared to participants with the lowest level of exposure. No significant association was seen between DMAPs, DEAPs, DAPs and asthma attacks. While results of this study suggest that organophosphates do contribute to a self-reported asthma diagnosis, more research is needed to determine its temporality.
Keywords: Environmental health; Asthma; Public health